FAKTOR SOSIAL EKONOMI PENENTU PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DAYA TARIK WISATA GUNUNG KERBAU - Stefen Topurmera; Heriyanus Jesayas; Michel J. Matatula (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
An important goal of status determining of Matras Tourism Village in 2010 was in order more people took participate in development programs of the local tourism sector. The relevant findings of previous research were that the socio-economic characteristics including knowledge and perceptions associated with participation. The purposes of the research were to study the socio-economic characteristics and perceptions, to study the shape and the level of participation, and to study the relationship between socio-economic characteristic and perception toward participation. The research was categorized as survey research that used purposive-snowball sampling. The data were analyzed by descriptive-qualitative, Scoring, Crosstabs, Chi-Square, and Spearman's Rank. Overall, 47,73% of respondents have moderate perception level. While, 38,64% of respondents have low participation level. All indicators were positively related to the participation, except for the age and the number of dependents (negatively). However, the relationship strength were different. The informal education, tourism knowledge, perception of institutional and funds budgeting were strongly related to participation (sig. 99%). While, the perception of planning product, object/attraction of tourism, support facilities, opportunity and competitiveness described sufficiently-strong relation to participation (sig. 95%).